1972
DOI: 10.1136/thx.27.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid atresia: Experience in surgical management with a modified cavopulmonary anastomosis

Abstract: A limited experience with an initial series of nine patients operated upon for tricuspid atresia using a modified superior vena cava to right pulmonary artery anastomosis is presented. The modified technique is described and illustrated. It avoids permanent disruption of pulmonary artery continuity and the high incidence of superior vena cava syndrome. In short, the right pulmonary artery is not severed, the azygos vein is always ligated, the superior vena cava is not mass ligated and is subjected to delayed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 3 publications
0
26
0
2
Order By: Relevance
“…An initial palliative procedure is often needed during early infancy to control the flow of blood to the lung, and to preserve eligibility for subsequent interventions. The bidirectional Glenn procedure and several modifications of the Fontan procedure have evolved as the standards of care for intermediate and long-term palliation [1][2][3][4][5][6][7][8][9][10][11][12][13]. Many patients have benefited from advances and refinements in these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…An initial palliative procedure is often needed during early infancy to control the flow of blood to the lung, and to preserve eligibility for subsequent interventions. The bidirectional Glenn procedure and several modifications of the Fontan procedure have evolved as the standards of care for intermediate and long-term palliation [1][2][3][4][5][6][7][8][9][10][11][12][13]. Many patients have benefited from advances and refinements in these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Após a descrição original da cirurgia de Glenn, sua aplicação clínica, de maneira a anastomosar a veia cava superior terminolateralmente à artéria pulmonar, foi feita por Azzolina et al, 7 em 1972. Na avaliação préoperatória do shunt cavopulmonar estagiado, é fun damental a documentação de pressões intravasculares pulmonares < 15 mmHg.…”
Section: Cateterismo Cardíaco Pré-cirurgia De Glennunclassified
“…From this publication onwards, other studies reported such complications 8,9 , decreasing the enthusiasm in regard to the classical Glenn operation, which was then abandoned in favor of the bidirectional Glenn operation 6,10 .…”
Section: Abstract Pulmonary Arteriovenous Fistulae Bidirectional Glementioning
confidence: 99%
“…Azzolina et al 6 performed that operation for the first time, which became known as the bidirectional Glenn operation. The major advantage of this technique was that the right pulmonary artery, not separated from the confluence, allowed the division of the blood volume of the superior vena cava between both lungs.…”
mentioning
confidence: 99%